2015
DOI: 10.14737/journal.jahp/2015/3.2.39.42
|View full text |Cite
|
Sign up to set email alerts
|

Oestrous Response and Conception Rate in Malabari Cross-Bred Goats Following Two Different Oestrus Synchronization Protocols

Abstract: | The comparative efficacy of two oestrus synchronization protocols using Ovsynch and progestagen (TRIU -C ® ) was analysed based on the reproductive performance in Malabari cross bred goats. Early onset of oestrus with higher oestrus response was observed in the progestagen group of animals. However, there was no significant difference between the two protocols, on the duration and intensity of oestrus. When diagnosed by ultrasound sonography, the conception rate following the two protocols did not find to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
2
9
1
Order By: Relevance
“…The relatively similar results were also reported by Pujar et al [1] in Indian goats (99.16%) and Holtz et al [10] in Boer goats (100.0%). The slightly different result was reported by Panicker et al [7] which obtained an estrous percentage of 75.0% in Malabari crossbreed goats that were induced with ovsynch protocol. In this study, the Kacang goat showed an unfavorable response to the implementation of estrous synchronization with PGF2α.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…The relatively similar results were also reported by Pujar et al [1] in Indian goats (99.16%) and Holtz et al [10] in Boer goats (100.0%). The slightly different result was reported by Panicker et al [7] which obtained an estrous percentage of 75.0% in Malabari crossbreed goats that were induced with ovsynch protocol. In this study, the Kacang goat showed an unfavorable response to the implementation of estrous synchronization with PGF2α.…”
Section: Resultscontrasting
confidence: 67%
“…Artificial insemination is carried out 12-16 hours after the second injection of GnRH [5]. The ovsynch protocol has been carried out on Saanen goats [6], Malabari Cross-Bred Goats [7], and Indian goats [1], but no one has used this protocol in Kacang Goat.…”
Section: Introductionmentioning
confidence: 99%
“…In arid areas where vegetation is scant and is too steep for cultivation, goats roaming more widely than other herbivores and meet their requirements from browsing on weeds neglected by others, they has higher tolerance to feed deficient in crude protein and certain minerals. Goat milk is cheap, wholesome, easily digestible and nutritious (Panicker et al, 2015). It is recommended for use in dyspepsia, peptic ulcer and pyloric stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there was a 28.8 million heads of sheep that produced 43.6 thousand tons of wool. Usually small flocks of sheep and goats are raised together in plains and sub hilly areas of Pakistan (GoP, 2013-14;Panicker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%